ANALISIS PERBEDAAN KINERJA KEUANGAN SEBELUM DAN SESUDAH RIGHT ISSUE PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2015-2023 - Tanjung, Abdul Hafiz; Julianti, Peni; Bhaktiar, R. Enough (E-Jurnal Akuntansi TSM, 2026)
This study aims to analyze the impact of a right issue on the financial performance of companies listed on the BEI, using the Return on Equity (ROE), Total Asset Turnover (TATO), Debt to Equity Ratio (DER), and Price Earnings Ratio (PER) ratios. Data analysis was conducted using the Paired Sample t-test and Wilcoxon Signed-Rank Test. A sample of 37 companies was obtained using a Random Sampling technique. The research findings reveal a significant difference in ROE and DER after the right issue. In contrast, no significant difference was found in TATO or PER. This indicates that the right issue has a positive impact on profitability and capital structure but is not significant for asset efficiency and stock valuation.